The causal effect of agritourism on farm survival - Matthias Firgo; Dieter Pennerstorfer (Johannes Kepler University of Linz, Department of Economics, 2023)
We use two waves of census data with detailed farm characteristics for the total population of Austrian farms to examine the causal effect of agritourism on farm survival. To account for self-selection into agritourism, we use regional variation in tourism intensity that is exogenous to individual farms. On average, agritourism causally increases survival probabilities by 10.3 percentage points over an eleven-year period, which is both large and statistically significant. Marginal effects vary by farm characteristics and are as large as 15.9 percentage points for some sub-populations. Agricultural policies to facilitate entry into agritourism can therefore be effective in keeping farms in the market. Our analysis shows that the magnitude of the estimated coefficients is heavily biased as long as we do not adequately account for endogenous self-selection into agritourism. This suggests that even with a big database, an appropriate identification strategy is required to obtain causal and thus policy-relevant estimates.
Keywords: Z30; Q12; L25; 330; agritourism; firm survival; agriculture; diversification; big data; bivariate probit